(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The combination of gemcitabine (GEM) and paclitaxel (PTX) are effective anti-cancer regimens due to their different mechanisms of action and partially non-overlapping toxicities. The present study aimed to elucidate a potential effect of folic acid-conjugated-Gemcitabine-Paclitaxel-loaded nanostructured lipid carriers (FA-GEM-PTX-NLCs) on the proliferation of cancer cell lines A549 for the management of resistant cancer. Cell uptake of NLCs in A549 cell lines was carried out with fluorescent dye, and Fluorescein isothiocyanate loaded NLCs (FITC-NLCs). Flow cytometry showed that FA-PTX-GEM-NLCs exhibited enhanced cellular uptake via folate receptor-mediated endocytosis. Cytotoxic effect (GI50) of formulations was measured by MTT assay method using A549 cells. Cytotoxicity results reveal that the GI50 of FA-GEM-PTX-NLCs was 2.16 μg/mL, which is three times less than the GI50 (6.48 μg/mL) GEM-PTX-NLCs. Furthermore, data obtained from the pharmacokinetics study explored the extended half-life and higher serum concentration of GEM and PTX when delivered through FA-PTX-GEM-NLCs compared to PTX-GEM-NLCs and free drugs. Tumor growth inhibition results advocate for the higher anti-tumor activity of FA-GEM-PTX-NLCs in A549 cell line induced tumor-bearing Balb/c mice by estimating tumor burden. In conclusion, the novel folic acid conjugated NLCs loaded with GEM and PTX could be used as a potential chemotherapeutic formulation for cancer management.